THE DETERMINANT EFFECT OF HEALTH BPJS FEE PAYMENT ON FEE COMPLIANCE OF INDEPENDENT JKN PARTICIPANTS - Surahmawati Surahmawati; Nurpratiwi Awalia Rahmat; Sukfitrianty Sahrir; Syamsul Alam (Universitas Islam Negeri Alauddin Makassar, 2020)
Background: JKN (National Health Insurance) is one of the government's efforts to improve public health status by requiring all Indonesians to become JKN members.Objective:This research aims to determine whether the determinant factor of fee payments has an effect on the compliance of Independent JKN participants in paying the fees.Method: A quantitative research with an analytic-observational approach and a cross-sectional research design. The population in this study was all the Independent JKN participants in Biringkanya sub-district, Makassar. The samples in this study were 52 families that were selected by using accidental sampling technique and the data collection method was carried out by using an online questionnaire via Google form.Result: The results of this study indicate there is an effect of the respondent's income (0.001), increase in contributions (0.005), the deadline for payment of contributions (0.011) on the compliance of JKN Mandiri participants in paying BPJS Health contributions, and there is no effect of education (0.723), employment (0.138) and contribution payment procedures (0.656) to the compliance of JKN Mandiri participants to pay BPJS Health contributions in the Biringkanaya sub-district, Makassar City in 2020.Conclusion:Adjusting the amount of fees, adding time limits and in-depth socialization to the community are some alternatives that can be used by providers, in this case by Health BPJS in increasing compliance to pay Health BPJS fees.